2013
DOI: 10.1016/j.archger.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Myosteatosis and myofibrosis: Relationship with aging, inflammation and insulin resistance

Abstract: The mechanisms impairing muscle quality and leading to myofibrosis (MF) and myosteatosis (MS), are incompletely known. In biopsies of paraspinous muscle (PM) of 16 healthy elderly men undergoing elective vertebral surgery, we histologically determined the area of MF and MS expressed as muscle quality index (MQI), in order to investigate the relation between them, as well as the main predictors of muscle quality. Total PM muscle area and intermuscular adipose tissue (IMAT) were evaluated by MRI and body composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 27 publications
4
81
0
2
Order By: Relevance
“…The degree of myofibrosis and myosteatosis that are the main predictors of quality of muscles is associated with aging and a pattern of increased adiposity. 41) Aging of skeletal muscle is associated not only with muscle atrophy and replacement of muscle by adipose tissue but also with an increase in fibrous connective tissue; similar results have been observed in obese condition. 41) In general, patients with sarcopenia have low weight and low BMI.…”
Section: Sarcopenic Obesitysupporting
confidence: 71%
See 1 more Smart Citation
“…The degree of myofibrosis and myosteatosis that are the main predictors of quality of muscles is associated with aging and a pattern of increased adiposity. 41) Aging of skeletal muscle is associated not only with muscle atrophy and replacement of muscle by adipose tissue but also with an increase in fibrous connective tissue; similar results have been observed in obese condition. 41) In general, patients with sarcopenia have low weight and low BMI.…”
Section: Sarcopenic Obesitysupporting
confidence: 71%
“…41) Aging of skeletal muscle is associated not only with muscle atrophy and replacement of muscle by adipose tissue but also with an increase in fibrous connective tissue; similar results have been observed in obese condition. 41) In general, patients with sarcopenia have low weight and low BMI. In contrast, patients with SO have high weight, low lean body mass, and high BMI.…”
Section: Sarcopenic Obesitysupporting
confidence: 71%
“…Furthermore, the associations among immunity, inflammation, and adipocytokines have recently been emphasized as key mechanisms by which sarcopenia affects patient survival. 17,26 We currently are implementing preoperative and postoperative nutritional and exercise therapeutic protocols, especially for patients with sarcopenia or with poor nutritional status. Although the ideal period of these perioperative therapies before and after operation is not established, in our opinion, at least 1 month before operation and a few months after operation are required to improve sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that loss of muscle tissue in sarcopenia is accompanied by infiltration with fat and connective tissue, a condition known as myosteatosis. 17 Assessments of skeletal muscle quality and intramuscular fat infiltration are therefore crucial for considering sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, skeletal muscle aging is associated with myofibrosis and myosteatosis and to gradual fibrous replacement in the muscle (29). In addition, recent histological studies have shown that high values of serum CRP seem to be related with reduced protein synthesis and increased protein catabolism (30).…”
Section: Chronic Inflammationmentioning
confidence: 99%